2013
DOI: 10.1155/2013/146352
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Controller for Mechatronic Sun Tracking System to Improve Performance

Abstract: An embedded system that contains hardware and software was developed for two-axis solar tracking system to improve photovoltaic panel utilization. The hardware section of the embedded system consists of a 32-bit ARM core microcontroller, motor driver circuits, a motion control unit, pyranometer, GPS receiver, and an anemometer. The real-time control algorithm enables the solar tracker to operate automatically without external control as a stand-alone system, combining the advantages of the open-loop and the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Analysis of these data revealed that the sun tracker generated 39.2% more energy than the fixed slope system. When compared, the generated energy efficiency is slightly less than [20,21,23]. The total generated energy is high than [23] also consumed energy by DC motors higher.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Analysis of these data revealed that the sun tracker generated 39.2% more energy than the fixed slope system. When compared, the generated energy efficiency is slightly less than [20,21,23]. The total generated energy is high than [23] also consumed energy by DC motors higher.…”
Section: Resultsmentioning
confidence: 89%
“…Naturally, it is possible only solar noon every day. By adjusting the PV panel to the sun starting from sunrise to sunset, the PV panel output performance may rise up to 46% when compared with fixed slope PV panel [20]. Sun rays' incidence angle changes largely diurnally and slightly seasonally.…”
Section: Case Study: Design Embedded Controller For Mechatronic Sun Tmentioning
confidence: 99%
“…b. The literature presents some constructive solutions of tracking mechanisms, mainly for individual PV panels [10,14,18,19,23,28,30]. In the case of the arrays/groups of panels there are only summary descriptions of different producers for such systems, for simple topologies (line -string) and single-axis systems (M=1) [47].…”
Section: Issn: 2668-0416mentioning
confidence: 99%
“…The photovoltaic efficiency evaluated by using the exergetic efficiency equation, it can be represents as the ratio of exergy useful (electrical exergy rate and thermal rate) on exergy of the solar radiation rate [14]: (3) Where, the input exergy or the solar radiations exergy is given by [14]: (4) And the exergy output of the solar PV module can be estimated as follows [14]:…”
Section: Exergy and Energy Efficienciesmentioning
confidence: 99%
“…They studied and optimized the cost-effective of a sun tracker controller and their results were that the two-axis tracker has increased the energy collected by 40.7% while the improvement of the system cost increased by 21.1% [4].…”
Section: Introductionmentioning
confidence: 99%